Forming and Framing Self-help Groups: A Practice Model for Post-disaster Social Work Intervention - K.C., Abhiyan; Rai, Sukrita (Nepalese Journal of Development and Rural Studies, 2024)
This paper aims to posit forming and framing the self-help groups (SHGs) as an interventional approach and crane tool to mitigate, reorganize, restore, and normalize intra-interpersonal and collective functioning in a post-disaster period. First, it presents a review of the conceptual problematization of disaster and post-disaster situations and its implications for social work intervention. Next, it shows self-initiated frameworks and interventional models initiated and followed by rural migrants appropriately suited to the contexts of restoring social functioning in post-disaster periods based on the lived experiences and narrations of rural migrants. This inquiry of lived experiences was based on thematic analysis outlined by Denzin and Lincoln and Chang et al. Criteria sampling was chosen, and 10 families of rural migrants were interviewed who faced similar life transitions and trajectories during and post-earthquake periods. Next, it identified three dominant themes: a) capability failure and gaining capability sets, b) rebuilding livelihood, social business and becoming solopreneur-entrepreneur, and c) forming and framing self-help group(s) and inclusive participation. Finally, this paper posits the forming and framing of SHGs from social business, entrepreneurship, capability, livelihood, and active meaningful participation as a practice model-interventional frame to help and uplift the social functioning of individuals, groups, and communities in post-disaster periods. In addition, it offers the implications of this practice, i.e., forming SHGs as a first step to tackle post-disaster earthquake situations by social workers and stakeholders and framing SHGs efficiently from the empirically grounded conceptualizations and practices initiated and followed by the sufferers during and in post-disaster periods.